Blockchain and Artificial Intelligence for Decentralized Edge Environments - Yuansong Qiao (Future Internet)
Edge environments typically involve multiple stakeholders and the management of decentralized devices and resources, presenting significant challenges related to the assurance of data security, real-time processing, and efficient coordination [...]